2019
DOI: 10.1891/1058-1243.28.4.210
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Knowledge, Attitudes, and Practices of Providers and Staff at Al-Zahraa University Hospital Regarding the Baby-Friendly Hospital Initiative and the International Code of Marketing Breast Milk Substitutes

Abstract: Four hundred eight providers and staff members who care for breastfeeding mothers and babies at Al-Zahraa University Hospital, Cairo, Egypt were randomly selected to assess their knowledge, attitudes, and practices regarding the Baby-Friendly Hospital Initiative. The majority of the participants scored above 50% on the knowledge and attitude questions, however, on the practice questions only 45.3% scored above 50%, similar to the result obtained 10 years prior. The results indicate that most attention should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Many different sorts of educational and training interventions were covered in the research. These were focused on improving both knowledge of breastfeeding, increasing support for the BFHI and improving attitudes towards breastfeeding [ 23 , 24 , 107 , 108 ] across many countries. Training improved hospitals’ compliance with the Ten Steps in Italy [ 108 ] the UK [ 109 ] and Canada [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many different sorts of educational and training interventions were covered in the research. These were focused on improving both knowledge of breastfeeding, increasing support for the BFHI and improving attitudes towards breastfeeding [ 23 , 24 , 107 , 108 ] across many countries. Training improved hospitals’ compliance with the Ten Steps in Italy [ 108 ] the UK [ 109 ] and Canada [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare workers who have inadequate knowledge may give misleading advice to mothers about breastfeeding. On the other hand, good knowledge may not always translate to good practice as observed in a previous study 19 …”
Section: Discussionmentioning
confidence: 79%
“…Some previous studies reported the majority of healthcare workers as having positive attitudes towards BFHI; however, the of attitude was not detailed. 18,19 Half of the healthcare workers in this study were considered to have good practice of BFHI, and the practice was significantly better among the nurses. This finding is not surprising, considering the pattern of knowledge and attitude among them as both knowledge and attitude are major determinants of practice.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations